Towards a corpus-based analysis of evaluative scales associated with even - Gast, Volker; Rzymski, Christoph (Linguistik Online, 2015)
Scalar focus operators like even, only, etc. interact with scales, i. e., ordered sets of alternatives that are referenced by focus structure. The scaling dimensions interacting with focus operators have been argued to be semantic (e. g. entailment relations, probability) in earlier work, but it has been shown that purely semantic analyses are too restrictive, and that the specific scale that a given operator interacts with is often pragmatic, in the sense of being a function of the context. If that is true, the question arises what exactly determines the (types of) scales interacting with focus operators. The present study addresses this question by investigating the distributional behaviour of the additive scalar particle even relative to scales whose focus alternatives are ordered in terms of evaluative attitudes (positive, negative). Our hypothesis is that such evaluative attitudinal scales are at least partially functions of the lexical material in the sentential environment. This hypothesis is tested by determining correlations between sentence-level attitudes and lexically encoded attitudes in the relevant sentences. We use data from the Europarl corpus, a corpus of scripted and highly elaborated political speech, which is rich in argumentative discourse and thus lends itself to the study of attitudes in context. Our results show that there are in fact significant correlations between (manual) sentence-level evaluations and lexical evaluations (determined through machine learning) in the textual environment of the relevant operators. We conclude with an outlook on possible extensions of the method applied in the present study by identifying attitudinal patterns beyond the sentence, showing that positively and negatively connotated instances of even differ in terms of their argumentative function, with positive even often marking the climax and endpoint of an argument, while negative even often occurs in qualifying insertions like concessive parentheses. While we regard our results as valid, some refinements and extensions of the method are pointed out as necessary steps towards the establishment of an empirical sentence semantics, in the domain of scalar additive operators as well as more generally speaking.